The effectiveness of the implementation of pile foundations on the example of the reactor building of a nuclear power plant with VVER-1000 - Akop E. Sargsyan; Elena G. Gukova (Structural Mechanics of Engineering Constructions and Buildings, 2020)
Aims. The purpose of this work is to justify the reliability of the developed models of pile foundations on the data of field observers and to demonstrate the feasibility of using pile foundations to increase the stability and bearing capacity of the NPP structures foundation using the example of reactor building (RB). Methods. The data of field observers for the settlement of the RB are presented. The expressions for calculation of the static stiffness of the contact surface of the slab bottom and soil medium, as well as for pile foundations taking into account the effects of interaction of grillage and pile field with the soil media with a general character of displacement of a circular cross section pile are submitted. A spatial three-dimensional finite element static model of RB was developed together with the soil base. Isolines of vertical movements of RB fundamental slabs for natural foundations, as well as for pile foundations for normal operation are shown. A comparative analysis of the data of field observers with the calculation results allows us to justify the reliability of the developed model of the pile foundation. Results. The calculations of the foundation yield correspond to all the period of operation including construction, and the results of observations relate only to the period of operation that explain the difference. A comparative analysis of the data of field observers with the calculation results allows us to justify of the strong effectiveness of realization of pile foundation for the massive structures on soft soil bases.